Deteksi Dini Sarkopenia Secara Dini Melalui Pemeriksaan Kekuatan Genggaman Tangan Dan Antropometri Pada Guru Dan Karyawan Sma Santo Yoseph, Cakung, Jakarta Timur - Santoso, Alexander Halim; Goh, Daniel; Sugiarto, Hans (Universitas Pahlawan Tuanku Tambusai, 2024)
Sarcopenia is a geriatric syndrome characterized by progressive loss of muscle mass and strength, which has a significant impact on the elderly and increases the risk of disability, decreased quality of life, and even death. The main risk factors for Sarcopenia include lack of physical activity, malnutrition, chronic disease, and aging. The purpose of this activity is to detect sarcopenia early through handgrip strength and anthropometry examinations. This activity was attended by 69 teachers and employees of Santo Yoseph High School, Cakung, East Jakarta. This activity was designed based on the PDCA method, which is a method consisting of planning, implementing, evaluating and continuously improving a process or activity. Based on the results of the calf circumference and handgrip strength examinations, 15 participants (21.74%) and 12 participants (17.39%) obtained results below normal. In addition, based on the results of the body mass index examination, 35 participants (50.72%) were obese, 17 participants (24.64%) were at risk of obesity, and 4 participants (5.8%) were underweight. Early detection of sarcopenia is essential to reduce its negative impact on health and reduce the burden on individuals and the health system. By holding this community service activity, it is hoped that there will be an increase in public awareness of the importance of preventing sarcopenia in order to prevent worsening of the condition and improve the quality of life of individuals.